Mechanics of solids and fluids - Ziegler, Franz (Springer-Verlag, 1995)
Suitable for courses on fluid and solid mechanics, continuum mechanics, and strength of materials, this title offers a presentation of the theories and practical principles common to various branches of solid and fluid mechanics.